2012
DOI: 10.1063/1.3654949
|View full text |Cite
|
Sign up to set email alerts
|

Efficient manipulation of microparticles in bubble streaming flows

Abstract: Oscillating microbubbles of radius 20-100 lm driven by ultrasound initiate a steady streaming flow around the bubbles. In such flows, microparticles of even smaller sizes (radius 1-5 lm) exhibit size-dependent behaviors: particles of different sizes follow different characteristic trajectories despite density-matching. Adjusting the relative strengths of the streaming flow and a superimposed Poiseuille flow allows for a simple tuning of particle behavior, separating the trajectories of particles with a size re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
95
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 48 publications
7
95
0
Order By: Relevance
“…They are greatly beneficial in a number of proposed applications in chemical, biological, and physical processes such as mixing, [149][150][151] pumping, 152,153 characterizing enzymatic reactions, 154 cell lysis, 155 and sorting and enrichment. 156,157 A thorough review article on applications of oscillating microbubbles in microfluidics is recently written by Hashmi et al 158 Although, there are a number of techniques to generate bubbles in microfluidic channels, 159,160 using a cavity is found to be the simplest. Upon generation of the bubble, a piezoelectric transducer can be coupled with the device to oscillate the bubble.…”
Section: A Cavitation Microstreamingmentioning
confidence: 99%
See 1 more Smart Citation
“…They are greatly beneficial in a number of proposed applications in chemical, biological, and physical processes such as mixing, [149][150][151] pumping, 152,153 characterizing enzymatic reactions, 154 cell lysis, 155 and sorting and enrichment. 156,157 A thorough review article on applications of oscillating microbubbles in microfluidics is recently written by Hashmi et al 158 Although, there are a number of techniques to generate bubbles in microfluidic channels, 159,160 using a cavity is found to be the simplest. Upon generation of the bubble, a piezoelectric transducer can be coupled with the device to oscillate the bubble.…”
Section: A Cavitation Microstreamingmentioning
confidence: 99%
“…165 The maximum streaming velocity, which is located near the bubble, can then be approximated from u s $ 2p 2 af . 155 However, in high applied voltages and typical applied frequencies in microfluidic systems 156,157 (15 kHz < f < 100 kHz), Re s $ 1 which makes the theoretical solution more complicated as the full Navier-Stokes equations must be solved. Nevertheless, RNW streaming can describe the flow in these cases quite accurately.…”
Section: A Cavitation Microstreamingmentioning
confidence: 99%
“…This will allow perform label-free imaging of the captured bio-targets using our device with a higher sensitivity as that can be achieved using the sensing mechanism described here and in our earlier work. 6,7 Wang et al 33 investigated the inertial effects due to vortical flow separation and due to the particles in such flow and found that oscillating microbubbles driven by ultrasound can initiate a steady streaming flow around the bubbles. This flow affects the microspheres' movement to exhibit size-dependent behaviors.…”
Section: E Comparison With Other Hydrodynamic Mechanismsmentioning
confidence: 99%
“…3,4 Particles are passed through a channel with a flow field driven by oscillating bubbles and pressure. The flow field becomes a combination of closed and open streamlines.…”
mentioning
confidence: 99%
“…The mechanism of the trapping and sorting arises from the differences between interactions of the particles with the fluid. [2][3][4][5][6][7][8] In particular, counter-rotating vortices have been used to sort particles and manipulate biopolymers. They have been used to deposit DNA precisely across electrodes 9 and trap DNA.…”
mentioning
confidence: 99%